2022
DOI: 10.3390/polym14214720
|View full text |Cite
|
Sign up to set email alerts
|

Sponges from Plasma Treated Cellulose Nanofibers Grafted with Poly(ethylene glycol)methyl Ether Methacrylate

Abstract: In this work, cellulose nanofibers (CNF) were surface treated by plasma and grafted with poly(ethylene glycol)methyl ether methacrylate (PEGMMA) for increasing mechanical strength and hydrophobicity. The surface characteristics of the sponges were studied by scanning electron microscopy, micro-computed tomography, and Fourier transform infrared spectroscopy, which demonstrated successful surface modification. Plasma treatment applied to CNF suspension led to advanced defibrillation, and the resulting sponges (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
1
1
0
Order By: Relevance
“…Additionally, for the 100% PEGMEMA 300 sample, there is a prominent peak near 2874 cm −1 indicative of C-H stretching in PEG [ 20 ]. For PEGMEMA 300 , similar peaks have been reported in previous papers [ 21 , 22 ]. As the molar percentage of PEGMEMA 300 increases from 0 to 100% in the formulation, the PEG C-H stretching peak at 2874 cm −1 increases.…”
Section: Resultssupporting
confidence: 87%
“…Additionally, for the 100% PEGMEMA 300 sample, there is a prominent peak near 2874 cm −1 indicative of C-H stretching in PEG [ 20 ]. For PEGMEMA 300 , similar peaks have been reported in previous papers [ 21 , 22 ]. As the molar percentage of PEGMEMA 300 increases from 0 to 100% in the formulation, the PEG C-H stretching peak at 2874 cm −1 increases.…”
Section: Resultssupporting
confidence: 87%
“…The images recorded following the cytotoxicity tests for the unmodified NC (NC/BE 4/0) and the NC with the highest amount of BE (NC/BE 4/4) are shown in Figure 11. One can observe that the cells developed normally in the presence of pure nanocellulose, an already established safe material [59], as well as in the presence of the sample containing the maximum amount of BE. Other tests followed the effect of basil extract on SH-SY5Y cells and revealed that the integrity of the cell's membrane decreased with the addition of basil extract at a 2 mg/mL concentration [60].…”
Section: Cytotoxicity Testsmentioning
confidence: 97%